PENGARUH MUTU PELAYANAN DAN CITRA RUMAH SAKIT TERHADAP LOYALITAS PASIEN SERTA KEPUASAN PASIEN SEBAGAI INTERVENING DI INSTALASI PERISTI RSD dr. SOEBANDI JEMBER - 1Siti Aminah; Dwi Cahyono Cahyono; Toni Herlambang (Jurnal Sains Manajemen dan Bisnis Indonesia, 2017)
ABSTRACTThe purpose of this study was to determine  impact of service quality and Hospital Image to loyalty patients through patient satisfaction peristi RSD dr. Soebandi Jember. This research is a quantitative research survey. With a sample of 110 respondents. The test instrument using validity and reliability. The analysis technique used is path analysis. From the analysis by using path analysis, obtained by the calculation results show that the variables of service quality significantly influence patient satisfaction, Hospital Image significant effect on patient satisfaction, quality of service significantly influence patient loyalty, Hospital Image significant effect on patient loyalty, satisfaction patients have a significant effect on patient loyalty. The image quality of care and Hospitals effect on patient loyalty through patient satisfaction with the value of their indirect effect is greater than the direct effect, with the influence of independent variables on the dependent variable in this study was 90.5% and the remaining 9.5% is explained by other variables that was not presented in this study.Keywords: Quality of Service, Hospital Image, Patient Patient Satisfaction and Loyalty